A user-concept matrix clustering algorithm for efficient next page prediction. (2016) - Hussein, Wedad; Gharib, Tarek F.; Ismail, Rasha M.; Mostafa, Mostafa Gadal-Haqq M.
Web personalisation is the process of customising a website's content to users' specific needs. Next page prediction is one of the basic techniques needed for personalisation. In this paper, we present a framework for next page prediction that uses user-concept matrix clustering to integrate semantic information into web usage mining process for the purpose of improving prediction quality. We use clustering to group users based on common interests expressed as concept vectors and search only the set of frequent patterns matched to a user's cluster to make a prediction. The proposed framework was tested over two different datasets and compared to usage mining techniques that search the whole set of frequent patterns. The results showed a 33% and 2.1% improvement in the average system accuracy as well as 6.6% and 7.3% improvement in the average system precision and a 6.5% and 1.7% in coverage for the two datasets respectively, within the same computation timeframe.